Optimization of electroplating thickness results for SS400 steel using the Taguchi method - Ahmad Adib Rosyadi; Firman Gustiawan; Mahros Darsin; Yuni Hermawan; Mochamad Asrofi (Jurnal POLIMESIN, 2022)
SS400 steel is steel with a low carbon content (max 0.17 %C) or low carbon steel. SS400 applications are widely used in the construction industry, railway industry, bridges and others. The use of SS400 which is in direct contact with the surrounding environment will cause the appearance, quality, and usefulness of the material or material to decrease. One way to prevent and improve metal performance is electroplating. This study used SS400 carbon steel with chrome coating. The parameters in this study are a voltage of 3, 6, and 9 Volts; the temperature of 45, 50, and 55 oC; and the time of 20, 25, and 30 minutes. The Taguchi method L9(33) was used to design the experiments. Analysis of variance (ANOVA) shows that factors of chroming time, voltage, and temperature contribute to coating thickness at the level of 40.615%; 24.951%; and 10.369%, respectively. The maximum thickness of 47.340 µm could be achieved when using combination factors of plating time of 30 minutes, at 9 Volts, and keeping the temperature of the solution at 50 oC.